2020
DOI: 10.3389/fpsyt.2019.00989
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Task-Related HRV Is Associated With Inhibitory Dysfunction Through Functional Inter-Region Connectivity of PFC in Major Depressive Disorder

Abstract: the left middle frontal gyrus and insula. However, the resting-state RMSSD value was not related to these significant difference functional connectivity networks in all participants. It concludes that the decreased task-related HRV is associated with inhibitory dysfunction through functional inter-region connectivity in the PFC in MDD, and the task-related HRV can be used as an index of the association between MDD and autonomic dysregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Low HRV has been associated with greater mortality 19 . In non-pregnant populations, low or excessive as well as unstable HF are associated with psychiatric diagnoses 12 , 20 , 21 . In addition to HF, other HRV measures have also been associated with anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low HRV has been associated with greater mortality 19 . In non-pregnant populations, low or excessive as well as unstable HF are associated with psychiatric diagnoses 12 , 20 , 21 . In addition to HF, other HRV measures have also been associated with anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have gone further to study the links between HRV and prefrontal cortex (PFC) function 12 , 28 30 . Important as both increased and decreased PFC functioning are linked to psychiatric diagnoses including MDD, bipolar disorder, obsessive–compulsive disorder (OCD), PTSD, and social phobia 20 , 31 34 .…”
Section: Introductionmentioning
confidence: 99%
“…In our population, VNS non-responders seem to be characterized by a sudden autonomic imbalance, a decrease in parasympathetic activity related to early seizure activity, possibly targeting areas of the central autonomic network. A recently published study involving HRV measurements in patients with major depression showed that a decreased task-related HRV is associated with inhibitory dysfunction in structures of the prefrontal cortex [28]. HRV measures are often used to assess the integrity of the central autonomic system and its contribution to recovery in severe disorders of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of PWH who presented with gastrointestinal symptoms observed that vagal dysfunction was associated with bacterial outgrowth in the small intestines that was, in turn, linked to greater systemic inflammation ( 54 ). Efferent vagal pathways that are modulated by decreases in depressive symptoms have the potential to alter the gut microbiota and decrease microbial translocation, as evidenced by the effects of vagal stimulation ( 55 , 56 ). Prior clinical research in people without HIV observed that increased vagal tone is an important indicator of a favorable response to cognitive-behavioral treatments for depression ( 57 , 58 ).…”
Section: This Is Now: Microbiome-gut-brain Axis Alterations Relevant ...mentioning
confidence: 99%